THE EMERGENCE OF CYBER RISKS, THEIR ESSENCE AND ECONOMIC CONSEQUENCES - KHOLBAEV A. YU. (International Journal of Artificial Intelligence for Digital Marketing, 2024)
The article describes the essence of information risk insurance, the current stages and specifics of information risk insurance. Insurance risks include insurance risks and uninsured benefits. Cyber-attacks are classified as damages that can be inflicted by committing cybercrimes. Information risk insurance programs are analyzed.